Reading readiness of kindergarten students in a Lebanese school. (c2017) - Bdeir, Maha F. (2017)
A growing body of research highlights the importance of the preschool period in preparing skilled readers. Phonological awareness is considered one of the key precursor skills to conventional literacy that develop during the preschool period. The purpose of the study is to investigate the impact of a systematic teaching of phonological awareness skills on the pre-reading skills of KG3 students in a private Lebanese school. Four KG3 sections, a total of 107 students, participated in the study. Two sections were selected to be the experimental group and received a twelve weeks intervention; the other two sections were the control group who were not taught phonological awareness skills. The design is quasi experimental; pre-tests were administered to the experimental and control groups. The former received the treatment; the latter did not. Post-tests were given to both groups in order to compare the results which revealed that all children in the experimental group exhibited significant improvement in all phonological awareness skills unlike those in the control group. Students‟ results in the experimental group also showed substantial improvement compared to their initial baseline performance results. Findings provide early childhood educators with an understanding of phonological awareness skills, ways of promoting their development at the preschool level and phonological age appropriate instruction to be integrated in the preschool curriculum. The benefit is for students to learn to read earlier and better in order to prevent reading difficulties at later stages.